Understanding the Nature of Oneness Experience in Meditators Using Collective Intelligence Methods - Van Lente, Eric; Hogan, Michael J. (Frontiers in Psychology, 2020)
Research on meditation and mindfulness practice has flourished in recent years. While much of this research has focused on well-being outcomes associated with mindfulness practice, less research has focused on how perception of self may change as a result of mindfulness practice, or whether these changes in self-perception may be mechanisms of mindfulness in action. This is somewhat surprising given that mindfulness derives from traditions often described as guiding people to realize and experience the non-separation of self from the world or its “oneness” with the whole of reality. The current study used a collective intelligence methodology, Interactive Management (IM), to explore the nature of oneness experiences. Five IM sessions were conducted with five separate groups of experienced meditators. Participants generated, clarified, and selected oneness self-perceptions they believed most characterized their experience both during meditation and in their everyday experience in the world. Each group also developed structural models describing how highly ranked aspects of oneness self-perceptions are interrelated in a system. Consistent themes and categories of oneness experience appeared across the five IM sessions, with changes in the sense of space (unboundedness), time, identity, wholeness, and flow highlighted as most influential. Results are discussed in light of emerging theory and research on oneness self-perception and non-dual awareness.